The correlation of the environmental dynamics of the southeastern periphery of the Poo zer ye (Valdai) glaciation in the Late Glacial and Holocene - Zernitskaya, Valentina P.; Vlasov, Boris P.; Matveev, Aleksey V.; Novik, Aleksey A.; Subetto, Dmitriy A.; Kublitskiy, Yuriy A.; Orlov, Alexandr V. (Journal of the Belarusian State University. Geography and Geology, 2020)
The landscape-climatic reconstruction in the southeastern sector of the last Scandinavian (Poozerye (Valdai)) glaciation was carried out within transect in the direction from Lake Naroch (Belarus) to the Lake Ilmen (Russia) based on palynological, isotopic and radiocarbon data. The first stage of deglaciation of the territory located between the maximum Orsha (Ostashkov) stage and the Vepsian-Krestetskiy marginal formations lasted from 20.0 to 15.5 cal. ka BP. The onset of lake sedimentogenesis in this region dates from the final stages of the Pleniglacial (16.5–15.5 cal. ka BP). The vegetation cover about 14.7 cal. ka BP represented by grass-shrub tundra. At the beginning of the Belling-Allered interstadial, there was an active expansion of tree species (birch, pine) to the north, following the retreating glacier. At the end of the Allered (13.3 cal. ka BP), open pine forests with birch dominated in the north of Belarus, and birch and pine-birch in the neighboring regions of Russia. The beginning of the expansion of spruce, both in Belarus and in the northwestern regions of Russia, dates from 13.2 cal. ka BP, which is comparable with the oscillation of Herzensee (GI-1b). Late Dryas cooling characterized by the spread of herb-forest-tundra landscapes, in which, apart from pine and birch, spruce played a significant role. The boundary Late Glacial ‒ Holocene (about 11.5 cal. ka BP) is marked by a decrease in the content of spruce pollen, shrubs of tundra and grass. According to isotopic and palynological data during the Holocene, revealed episodes of cooling. Changes in vegetation occurred in the following sequence: birch and pine-birch forests (11.5‒10.0 cal. ka BP), mixed birch-pine with the participation of broadleaved species (10.0 ‒8.0 cal. ka BP), coniferous-broadleaved (8.0 ‒5.8 cal. ka BP), broadleaved ‒ dark coniferous (5.8‒2.7 cal. ka BP), dark coniferous and oak ‒ dark coniferous with birch forests (2.7 cal. ka BP ‒ modern stage).
Keywords: ice sheet; deglaciation; paleolandscapes; Late Glacial; Holocene